Associations between cerebral blood flow and progression of white matter hyperintensities - Thammasart, Siriluk; Harvey, Danielle J.; Maillard, Pauline; DeCarli, Charles; Donnay, Corinne A.; Wheeler, Gregory J.; Fan, Audrey P. (Frontiers in Neuroimaging, 2025)
IntroductionIn an aging population, white matter hyperintensities (WMHs), observed on FLAIR MRI sequences, are indicators of cognitive decline, motor impairment, and increased vascular risk. However, the pathophysiological mechanisms underlying WMHs, including dynamic changes in cerebral blood flow (CBF) within and adjacent to lesions, remain poorly understood.MethodsOur study examined a diverse cohort of 300 elderly participants through arterial spin labeling (ASL) on 3 Tesla MRI, analyzing both cross-sectional and longitudinal data. We characterized the relationship between CBF and WMH development in different lesion locations (based on distance from ventricles) and brain tissue types (WMH lesion, penumbra, and normal white matter).ResultsOur findings reveal that WMHs exhibit significantly lower relative CBF (rCBF) compared to penumbra, normal-appearing white matter, and gray matter, with juxtaventricular WMHs (JVWMH) displaying the most substantial reductions. Longitudinally, WMHs that increased in size over a two-year period had lower baseline rCBF than those that remained stagnant, particularly in juxtaventricular and periventricular regions.DiscussionThis study not only highlights the predictive value of rCBF in WMH progression but also provides location-specific hemodynamic information about WMHs that can guide clinical management of WMH-related brain changes and their clinical manifestations.